Decreased lncRNA SNHG16 Accelerates Oxidative Stress Induced Pathological Angiogenesis in Human Retinal Microvascular Endothelial Cells by Regulating miR-195/mfn2 Axis - Zhang, Rui; Ma, Xiaoying; Jiang, Lei; Xia, Wenzhen; Li, Haipeng; Zhao, Na; Cui, Ximing; Zhang, Nan; Zhou, Huimin; Xu, Shunjiang (Current Pharmaceutical Design, 2021)
Background: This study was performed to identify the alterations of Long non-coding RNAs (lncRNAs) induced by oxidative stress and investigate the functional roles of SNHG16 in the pathological angiogenesis by human retinal microvascular endothelial cells (HMRECs). Methods: The expression profiles of lncRNAs and mRNAs induced by oxidative stress were identified by RNA-Seq, and the dysregulation of 16 lncRNAs including SNHG16 was verified in H2O2-treated human umbilical vein endothelial cells (HUVECs). Luciferase reporter assay and RIP analysis were used to investigate the binding relationship of SNHG16 to miR-195. Results: We confirmed that over-expression of SNGH16 attenuated H2O2-induced angiogenesis by HMRECs. In addition, SNHG16 was significantly decreased, whereas miR-195, a predictive target of SNHG16, was upregulated in H2O2, HG, and AGE-treated HMRECs. The binding relationship of SNHG16 to miR-195 was subsequently verified by luciferase reporter assay and RIP analysis. SNHG16 cotransfection abolished miR-195-mediated repression on mitofusin 2 (mfn2) protein level and counteracted the inductive effect of miR-195 on angiogenesis by HMRECs. Conclusion: These results indicated that decreased SNHG16 accelerates oxidative stress-induced pathological angiogenesis in HMRECs by regulating the miR-195/mfn2 axis, providing a potential target for diabetic retinopathy (DR) therapy.
Keywords: long non-coding RNA